Ecology and evolution of flowers - Harder, Lawrence D.; Barrett, Spencer Charles Hilton (Oxford biology., 2006)
The reproductive organs and mating biology of angiosperms (flowering plants) exhibit greater variety than those of any other group of organism, and floral traits provide some of the most compelling examples of evolution by natural selection. Given this diversity, a more strategic approach to their study is required which seeks to unravel general principles concerning the role of ecological function in the evolution of reproductive diversity. Harder & Barrett adopt just such an. approach to expose new insights into the functional basis of floral diversity. Major sections of the book in turn exa.